SEGUNDAS JORNADAS DE INVESTIGACIÓN DE LA FACULTAD DE CIENCIAS SOCIALES UNIVERSIDAD DE COSTA RICA - Martínez Herrera, Manue (Universidad de Costa Rica, 2020)
This publication is a significant sample of the heritage and academic work of the Faculty of Social Sciences of the UCR, of the set of experiences accumulated over decades of teaching, research and social action, of the historical and conjunctural concerns and demands that as a society we undertake; as well as new theoretical and methodological ventures that challenge our disciplinary fields. It is an opportunity to investigate in the field of social sciences, as a way of understanding one's limits and visualizing the development opportunities offered by multidisciplinary and multiparadigmatic work.